2018
DOI: 10.3390/ijms19071886
|View full text |Cite
|
Sign up to set email alerts
|

GPCRs in Cancer: Protease-Activated Receptors, Endocytic Adaptors and Signaling

Abstract: G protein-coupled receptors (GPCRs) are a large diverse family of cell surface signaling receptors implicated in various types of cancers. Several studies indicate that GPCRs control many aspects of cancer progression including tumor growth, invasion, migration, survival and metastasis. While it is known that GPCR activity can be altered in cancer through aberrant overexpression, gain-of-function activating mutations, and increased production and secretion of agonists, the precise mechanisms of how GPCRs contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 134 publications
(201 reference statements)
1
50
0
Order By: Relevance
“…Key therapeutic applications involving GPCRs include opioid analgesics, antihistamines, anticholinergics, typical and atypical antipsychotics, antimigraine drugs, β2-agonists for asthma, and anti-hypertensives [8]. However, anti-cancer drugs that specifically target GPCRs are not currently available [9]. The prostanoid receptors represent the most notable family of validated pharmacological targets in a variety of diseases, including cancer [10].…”
mentioning
confidence: 99%
“…Key therapeutic applications involving GPCRs include opioid analgesics, antihistamines, anticholinergics, typical and atypical antipsychotics, antimigraine drugs, β2-agonists for asthma, and anti-hypertensives [8]. However, anti-cancer drugs that specifically target GPCRs are not currently available [9]. The prostanoid receptors represent the most notable family of validated pharmacological targets in a variety of diseases, including cancer [10].…”
mentioning
confidence: 99%
“…Recent studies demonstrated that ARRDC3 also play roles in human cancer signaling [54,55]. We identified ARRDC3 as an important positive regulator in NAFLD and NASH.…”
Section: Resultsmentioning
confidence: 80%
“…Different types of melanomas occur because of various mutations. 16,17 The signaling pathways downstream from GPCR include the activation of protein kinase C family members and the release of diacylglycerol. 12,13 G-protein-coupled receptor (GPCR) proteins comprise a diverse family of transmembrane receptors, which exert a function of transducing signal from extracellular environment to the cellular interior.…”
Section: Introductionmentioning
confidence: 99%